The Role of Media in the Dynamics of Relationship between Muslims and Buddhism in the Post-Conflict in Tanjung Balai City, North Sumatra Province - Muhammad Jailani Irwansyah (STAB Kertarajasa, 2022)
Still fresh in mind, the violent conflict that took place in Tanjung Balai in July 2016. The violent conflict was mentioned in various mass media because of a protest of a Tionghoa woman to her neighbor about the call to prayer from the mosque in front of her house grew louder. After the open conflict in Tanjung Balai, the media has a very important role in building positive relations or also dividing the community in negative relationships between religious communities, reporting in print and online media has always been a reference for people who believe in the truth of the news. The article, believed to be the work of journalism, was then copied and distributed by some people through social media; WhatsApp, Facebook, etc. Then the writer tries to analyze the role of the media through its reporting in building relations between Muslims and Buddhists in Tanjung Balai after the open conflict in July 2016. This analysis uses a media framing approach. In analyzing the role of the media, the three media play more a role of a mirror of events in society and the world, implying a faithful reflection and the role of the window of events and experience. The role of filters is played more in the interests of the media, not in the interests of peace and relations between Islam and Buddhism going forward. For this reason, it is important to do mass media literacy and social media aimed at improving media skills that must be mastered by the community, improving lives and improving the lives of individuals who are mostly exposed to various kinds of information.